Factors that influence revisit intention based on tourist perceptions in Bali - Evelyn, Aurelia; Rahayu, Siti; Megawati, Veny (Faculty of Business and Economics, University of Surabaya, 2024)
The presence of smart tourism technology in Indonesia has brought forth numerous innovations in creating memorable vacation experiences, especially in the current era. Bali, being one of Indonesia's popular islands with a variety of attractions, has experienced the impact of smart tourism. This is evident in tourists booking flights online. This study aims to analyze the influence of perceived smart tourism technology (PSTT) on travel experience satisfaction, tourists' happiness, and revisit intention in Bali. The research is quantitative and involves four variables: perceived smart tourism technology, travel experience satisfaction, tourists' happiness, and revisit intention, with a total of 167 respondents who have vacationed in Bali within the past year. The data were processed using SEM with SPSS and SmartPLS. The research findings indicate that PSTT significantly and positively influences travel experience satisfaction. Travel experience satisfaction has a significant positive impact on tourists' happiness and revisit intention in Bali, while tourists' happiness also significantly and positively influences revisit intention.